Properties of construction material based-Diss fibers: Physico-mechanical characterisation - Zaid, Ismahen; Merzoud, Mouloud; Benazzouk, Amar (Journal of Building Materials and Structures, 2022)
In the building sector, issues related to sustainable development have become a major concern. The choice of materials has fundamental importance since it has a considerable influence on the energy consumption of the building and also on the overall environmental impact of the construction. Materials reinforced with vegetable fibres and/or particles are currently considered amongst the most promising materials in sustainable engineering technologies due to their several potential applications. In addition to its sustainable credentials, the application of these elements is interesting as they exhibit a set of important advantages, such as wide availability at relatively low cost, bio-renewability, ability to be recycled, biodegradability, non-hazardous nature, zero carbon footprint, and interesting hygro-thermal and mechanical properties. The viability of using vegetable Diss fibers for developing a sustainable lightweight construction material was investigated in this paper. The produced specimen contained 4/1 volume ratio of Diss fibers to Binder. In order to mitigate the inhibitory effect exerted by vegetable materials on binder hydration, Diss fibers were treated with hot water, while air lime-based Tradical PF70 binder has been selected to replace traditionally used cementitious binder. The study conducted on hardened material properties has indicated that despite a significant reduction in mechanical strength, the material exhibits higher residual stress that highlighted a ductile behaviour, compared to the reference specimen containing neat binder without Diss fibers.